Acute stroke imaging selection for mechanical thrombectomy in the extended time window: is it time to go back to basics? A review of current evidence. Issue 3 (3rd February 2022) - Fladt, Joachim; d'Esterre, Christopher D; Joundi, Raed; McDougall, Connor; Gensicke, Henrik; Barber, Philip
Abstract : Treatment with endovascular therapy in the extended time window for acute ischaemic stroke with large vessel occlusion involves stringent selection criteria based on the two landmark studies DAWN and DEFUSE3. Current protocols typically include the requirement of advanced perfusion imaging which may exclude a substantial proportion of patients from receiving a potentially effective therapy. Efforts to offer endovascular reperfusion therapies to all appropriate candidates may be facilitated by the use of simplified imaging selection paradigms with widely available basic imaging techniques, such as non-contrast CT and CT angiography. Currently available evidence from our literature review suggests that patients meeting simplified imaging selection criteria may benefit as much as those patients selected using advanced imaging techniques (CT perfusion or MRI) from endovascular therapy in the extended time window. A comprehensive understanding of the role of imaging in patient selection is critical to optimising access to endovascular therapy in the extended time window and improving outcomes in acute stroke. This article provides an overview on current developments and future directions in this emerging area.